The Invertebrate-Derived Antimicrobial Peptide Cm-p5 Induces Cell Death and ROS Production in Melanoma Cells - Ernesto M. Martell-Huguet; Daniel Alpízar-Pedraza; Armando Rodriguez; Marc Zumwinkel; Mark Grieshober; Fidel Morales-Vicente; Ann-Kathrin Kissmann; Markus Krämer; Steffen Stenger; Octavio L. Franco; Ludger Ständker; Anselmo J. Otero-Gonzalez; et al. (Marine Drugs, 2025)
Nowadays, healthcare systems face two global challenges: the rise of multidrug-resistant pathogens and the growing incidence of cancer. Due to their broad spectrum of activities, antimicrobial peptides emerged as potential alternatives against both threats. Our group previously described the antifungal activity of the α-helical peptide Cm-p5, a derivative of the natural peptide Cm-p1, isolated from the coastal mollusk Cenchritis muricatus; however, its anti-cancer properties remained unexplored. Analyses through calorimetry and molecular dynamics simulations suggest the relevance of phosphatidylserine for the attachment of Cm-p5 to cancer cell membranes. Cm-p5 exhibited cytotoxic activity in a dose-dependent manner against A375 melanoma cells, without toxicity against non-malignant cells or hemolytic activity. DAPI/PI and DiSC3(5) staining confirmed permeabilization, disruption, and depolarization of A375 cytoplasmic membranes by Cm-p5. Furthermore, Annexin V-FITC/PI assay revealed the induction of cellular death in melanoma cells, which can result from the cumulative membrane damage and oxidative stress due to the overproduction of reactive oxygen species (ROS). Moreover, after the treatment, the proliferation of A375 cells was dampened for several days, suggesting that Cm-p5 might inhibit the recurrence of melanomas. These findings highlight the multifunctional nature of Cm-p5 and its potential for treating malignant melanoma.